Misogyny on social media platform X: Discourse on the case of sexual harassment against a woman in a mosque - Prawitasari, Kirana; Maryani, Eni; Karimah, Kismiyati El (Jurnal Informatio, 2025)
Backgruond: The X social media account @detikcom posted a news report about a sexual harassment case experienced by a woman at Al-Ikhsan Mosque in Gorontalo. The post sparked various responses from netizens, ranging from support for the victim to comments blaming women. Purpose: This study aims to understand how misogynistic discourse is formed and develops in digital spaces, particularly on X, when discussing cases of sexual harassment in public domains. Methods: This research adopts a qualitative approach using the netnographic method. Data were collected from netizen comments on @detikcom’s X post published on March 1, 2024, as well as interviews with a gender expert and netizens who commented. Results: In this study, these comments were analyzed through the lens of feminist standpoint theory to uncover patriarchal perspectives reflected in responses toward female victims to highlight the social positioning of women as subjects often subordinated within societal structures. These comments not only shift the focus from the perpetrators, but also have implications for strengthening social norms that restrict women’s freedom to practice their religion and participate in the public sphere. Nonetheless, the study also found comments expressing empathy and defending the victim, rejecting misogynistic narratives. This research demonstrates that social media serves as a critical arena for reinforcing and challenging patriarchal values. The findings underscore the importance of critical awareness in addressing gender-based violence discourse online, as well as the need for educational interventions and platform policies that foster safer, more equitable spaces for victims.